Toys R Us : re-branding for the future (A) - Jurney, Susan; Burke, Melissa; O'Rourke, James S., 1946- (London : SAGE Publications Ltd, 2017)
Faced with declining market share, stock value and customer base, the new CEO for Toys R Us moves to rebrand the organization by improving the look of its stores and opening a 101,000 square-foot flagship store in Times Square, New York. He also heads up creation of exclusive merchandise, and focuses on the companys new primary target. A new logo is created, which includes the World Trade Center; new advertising is fashioned with footage with the World Trade Center in them. But all that must change after September 11, 2001. How can Toys R Us adapt its communications as a result of this national disaster?
Originally published: Jurney, S., Burke, M., & ORourke, J. S. (2003). Toys R Us: Re-branding for the future (A).02-03 A. Notre Dame, IN: The Eugene D. Fanning Center for Business Communication, Mendoza College of Business, University of Notre Dame.
Includes bibliographical references and index.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Toys "R" Us (Firm); Toy industry -- United States -- Case studies; Private equity -- United States -- Case studies; Branding (Marketing) -- United States -- Case studies